Factors involved in the development of diaper‐area granuloma of the aged. Issue 12 (4th December 2013) - Isogai, Rieko; Yamada, Hidekazu
Abstract An infant skin disease with clusters of nodules in the diaper contact area was reported as granuloma gluteale infantum. Recently, the number of elderly patients with this condition has increased, and it has been reported as diaper‐area granuloma of the aged. These lesions are presumably caused by irritation from feces and urine. We observed similar cutaneous symptoms in six elderly patients, five of whom revealed clusters of nodules arranged in a circular pattern in the gluteal region presenting a peculiar clinical picture. They were all bedridden and wore cloth diapers. We speculate that wearing a cloth diaper seems to be a major factor behind this condition. Another factor was sitting during the day. A subject had lesions with nodules on the scrotum. The distribution of nodules appeared to be related to the body position and vigorous movement of the patient. In all cases, topical steroid therapies were not effective. They were all positive for bacteriuria. Chronic urinary tract infection further irritates the skin. It is necessary to reduce urine contact and keep the lesion clean.